Soil organic matter dissolution and biodegradation batch studies - Ancorda, Joanna Lyn D.
Soil Organic Matter (SOM) is an allochthonous source of organic matter that comes in contact with the surrounding water through leaching and various biochemical transformations. Organic matter present in all surface, ground and soil waters is a major water quality issue posing health related concerns. This research aimed to better understand the extent and effect of SOM dissolution into the underlying water and to determine the role of biodegradation on the changes induced by dissolution. Batch reactors, in the form of serum bottles filled with soil and water, were incubated on a constant shaking rate under different temperatures and redox conditions. Sterile and non-sterile treatments were employed to determine SOM dissolution and dissolved SOM biodegradation, respectively. Results revealed no lag dissolution of SOM which exhibited continuous increase on ultraviolet absorbance at 254 nm (UVA254) values for the first nine days of incubation. A significant variation was observed between temperature and UVA254 which recorded higher SOM dissolution on 20ºC than 15ºC (F = 7.248; p = 0.008). Humic-, fulvic- and tryptophan-like fluorescence confirmed existence of SOM in water samples (FR≤ 1.5). Fifty to seventy five percent of dissolved SOM were degraded at the end of the batch experiments. Strong positive correlations were found between sterile and non-sterile treatments that made biodegradation a key parameter to offset the dissolution of SOM in water